The expression x( x - 4 ) when expanded is x² - 4x
An expression, often known as a mathematical expression, is a finite collection of symbols that are well-formed in accordance with context-dependent principles.
When a bracket is expanded, each term is multiplied by the expression outside of the bracket.
The distributive property states that multiplying the sum of two or more addends by a number yields the same outcome as multiplying each addend separately by the number and combining the resulting products.
Consider the expression,
x( x - 4 )
Let us assume y = x( x - 4 )
Using the distributive property, a( b + c ) = ab + ac
y = x( x - 4 )
y = x · x - x · 4
y = x² - 4x
Therefore, x( x - 4 ) = x² - 4x
Therefore, the expression when expanded is x² - 4x.
Learn more about expression here:
brainly.com/question/1859113
#SPJ1
Answer:
70.6
Step-by-step explanation:
The mean is the average of a set of numbers.
To find it, add up all the terms and divide it by the number of terms.
70 + 67 + 79 + 66 + 64 + 80 + 64 + 75 = 565
565 / 8 = 70.625
Rounding this to the nearest tenth, we get an answer of 70.6
A mountaineer climbed 1000 feet at a rate of x feet/hour
1000 = x ( t 1 ) eq1
5000 = X ( t 2) eq2 ( he climbed additional at different rate )
the rate was 10 feet / hour less than twice the first rate
X = 2x - 10 eq3
take eq1 and eq 2
( total time = t 1 + t 2 = T)
T = 1000/x + 5000/X
but X = 2x-10
T = 1000/x + 5000/( 2x -10)
T = 1000/x + 5000/( 2(x-5))
T = 1000/x + 2500 / (x-5)
Answer:
<h2><u><em>
Both classes will have the same value for the third quartile</em></u> </h2>
Step-by-step explanation:
This is it because the 3rd quartile is where the maximum or whisker is. Hope this helps!